2009
DOI: 10.1021/jf803090c
|View full text |Cite
|
Sign up to set email alerts
|

Initial Studies on the Quantitation of Bruise Damage and Freshness in Mushrooms Using Visible-Near-Infrared Spectroscopy

Abstract: Identification of mushrooms that have been physically damaged and the measurement of time elapsed from harvest are very important quality issues in industry. The purpose of this study was to assess whether the chemical changes induced by physical damage and the aging of mushrooms can: (a) be detected in the visible and near infrared absorption spectrum and (b) be modeled using multivariate data analysis. The effect of pre-treatment and the use of different spectral ranges to build PLS models were studied. A mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 27 publications
1
31
0
1
Order By: Relevance
“…36 However, consumer preference for fresh produce makes the management of PPO activity a 37 problem in the production, distribution and retail of fresh mushrooms. 38 Hyperspectral imaging (HSI) is a rapid and non-destructive technology that has recently 39 emerged as a powerful process analytical tool for food analysis (11). Hyperspectral images 40 are composed of hundreds of contiguous wavebands for each spatial position of an object.…”
Section: Introductionmentioning
confidence: 99%
“…36 However, consumer preference for fresh produce makes the management of PPO activity a 37 problem in the production, distribution and retail of fresh mushrooms. 38 Hyperspectral imaging (HSI) is a rapid and non-destructive technology that has recently 39 emerged as a powerful process analytical tool for food analysis (11). Hyperspectral images 40 are composed of hundreds of contiguous wavebands for each spatial position of an object.…”
Section: Introductionmentioning
confidence: 99%
“…Esquerre et al [81] used VIS and NIR absorption spectra to detect bruises and evaluate the freshness. The partial least-square model was employed and it was mostly influenced by changes in water matrix and enzymatic browning.…”
Section: A23 Freshnessmentioning
confidence: 99%
“…Vegetables, mushrooms, and fungi can suffer physical damages for too rough handling. VIS/NIR absorption seems to be useful for quantifying bruise damages for mushrooms [81,84].…”
Section: A25 Structural Characteristicsmentioning
confidence: 99%
“…Modeling damage in mushrooms has been reported in literature in recent times (Gowen et al 2008a, b;Esquerre et al 2009;O'Gorman et al 2010;Taghizadeh et al 2010) using different techniques including fourier transform infrared spectroscopy, hyperspectral imaging and near infrared spectroscopy coupled with chemometrics. These studies yielded models with low error rates for predicting damage in mushrooms highlighting the usefulness of imaging and spectroscopy for detecting physical damage in mushrooms, with the possibility of using these tools to develop classification systems for the industry.…”
Section: Partial Least Squares-discriminant Analysis (Pls-da)mentioning
confidence: 99%
“…Recent studies have demonstrated a number of spectroscopic and imaging techniques as being important tools for the investigation of various mushroom quality-related issues, such as mechanical damage (Esquerre et al 2009;O'Gorman et al 2010), freeze damage detection ) and detection of mushroom diseases (Gaston et al 2010); however, there is a need to investigate specific metabolites and metabolic pathways that may be related to browning in order to understand it fully. Metabolomics (GC/MS) coupled with chemometrics has not to the authors knowledge been used to detect damage in mushrooms; however it has been used as a tool in the food industry for similar use for e.g.…”
Section: Introductionmentioning
confidence: 99%